Quality assurance in distance education: The surrey MA (TESOL) experience - Mann, Charles C. (Animo Repository, 1998)
Despite widespread scepticism and occasional outright hostility from the educational establishment…Individuals desirous of enhancing their own opportunities and governments seeking greater returns on public investment in education have embraced the methods of distance education with enthusiasm. These methods make possible the rapid and inexpensive provision of instruction of consistent quality to large and scattered populations. (Daniel 1991, p. 38)